Medical Device Guidebook: A browser information resource for medical device users. (March 2017) - Clarkson, Douglas M.
Highlights: Provides a means of communicating potential risks of medical equipment to device users. Provides a means of collecting and communicating user experience of device use. Provides a means of providing access to device use information. Provides direct access to training resources. Allows communication of medical device users with trained device specialists. Abstract: A web based information resource – the 'Medical Device Guidebook' – for the enabling of safe use of medical devices is described. Medical devices are described within a 'catalogue' of specific models and information on a specific model is provided within a consistent set of information 'keys'. These include 'user manuals', 'points of caution', 'clinical use framework', 'training/assessment material', 'frequently asked questions', 'authorised user comments' and 'consumables'. The system allows identification of known risk/hazards associated with specific devices, triggered, for example, by national alerts or locally raised safety observations. This provides a mechanism for more effective briefing of equipment users on the associated hazards of equipment. A feature of the system is the inclusion of a specific 'Operational Procedure' for each device, where the lack of this focus is shown in the literature to often be a key factor in equipment misuse and associated patient injury. The 'Guidebook' provides a mechanism for the development of an information resource developed within local clinical networks and encourages a consistent approach to medical device use.